O Diário de Leituras no Ensino Fundamental: um incentivo ao Letramento Literário - Lisboa, Márcia Ferreira (2016)
Starting from the verification of a considerable index of failures in Secondary School of a municipal school from Goianinha/RN, it was found that a significant proportion of students have difficulties concerning reading. Thus, it is necessary to review the teaching of reading in schools, especially the teaching of literary reading, which should be seen as an ally to reverse this scenario. In this perspective, the objective of this study is to promote literary literacy in the eighth grade classes, using daily readings as an instrument to contribute to the formation of an active reader, who knows how to interact and to express their view of the different realities. Therefore, we intend to encourage the reading of literary texts, through the horror genre, in order to motivate the student to the habit of reading and producing texts; to allow the daily readers to make their literary reading with freedom, emphasizing what seems most significant to them; to improve the critical position of the reader by dialoguing with different readers and readings. The literary language shows all its potential, besides assisting in the processes of acquisition and expansion of reading and writing, corroborates the formation of the individual, developing a humanizing role. In this sense, in light of the theoretical assumptions of Soares (2009), Cosson (2014), Candido (1995), National Curriculum Standards of Portuguese Language (1998), Machado (1998), Buzzo (2003), Massol and Esposito (2012) among others, we propose a intervention project based on a reading journal, using the research-action methodology, as well as the concepts of Thiollent (1996). Reading journals proved to be an important tool to encourage literary literacy in schools. Since the use of writing is inherent in the making of the journal, we identified that linking reading to writing provided us a better understanding of the students' reading processes, since they have expressed in writing their understanding of the work. The results obtained showed that the literature of fear, represented by book Tales Seven bones and a curse, by Rosa Amanda Strausz, hooked the young readers, who learned to share their reading and to express their look through the journals. We achieved our goal to encourage literary literacy and to provide students opportunities for reading, socialization and freedom of expression.